A Functional Polymorphism (rs6265, G>A) of Brain-Derived Neurotrophic Factor Gene and Breast Cancer: An Association Study - Iqbal, Mehir un Nisa (Breast Cancer (Auckl), 2019)
PURPOSE: The objective of this study was to evaluate the relationship between brain-derived neurotrophic factor (BDNF) gene (Val66Met, rs6265, G>A) polymorphism and breast cancer (BC) among females of Southern Pakistan. METHODS: This case-control study consisted of 300 females (BC cases [n = 100] and controls [n = 200]) with age range of 18 to 45 years. All participants were recruited during January to December 2014 and were screened for depression using Zung depression scale. Isolation of genomic DNA (gDNA) followed by polymerase chain reaction-restriction fragment length polymorphism (PCR-RFLP) analysis was done. All statistical analysis was carried out on IBM-SPSS version 22 at P-value <.05. Hardy-Weinberg equilibrium (HWE), Pearson chi-square, and odds ratios (ORs) with 95% confidence interval (95% CI) were calculated. RESULTS: Genotype distribution of BDNF gene polymorphism lies in the goodness-of-fit model among controls. The statistical analyses reveal a significant association between genotype frequencies (χ(2) = 12.709, P-value = .002) of BDNF and BC among cases and controls. The AA genotype (OR = 5.2, 95%CI = 0.632-42.804) increases the risk of having BC. CONCLUSIONS: Our results suggest that BDNF gene polymorphism may have an association with BC risk among Pakistani females. However, the present finding needs to be replicated with greater sample size with BC risk.